Quantification of methane bubbles in shallow freshwaters using horizontal hydroacoustical observations. (29th June 2015) - Frouzova, Jaroslava; Tušer, Michal; Stanovsky, Petr
Abstract: Methane represents an important greenhouse gas, and its ebullition is a significant way of releasing gas from bottom sediments of shallow fresh waters to the atmosphere. Estimation of ebullition is complicated because of high spatiotemporal variability; however, a hydroacoustical survey represents an effective method for quantifying it. Commonly used vertical beaming in deep waters can be quite limited in very shallow waters. This study was thus aimed to investigate the possibility of using a horizontally oriented sonar beam for gas bubble quantification. Artificially prepared methane bubbles of various sizes, ranging from 2.5 to 905 × 10 −3 mL (1.7–12 mm of equivalent spherical diameter), were released from a depth of 6 m in a freshwater reservoir. The acoustic target strength (TS) of these bubbles was observed using both the vertical and horizontal beams of a 120 kHz frequency split‐beam sonar. TS obtained in both the vertical and horizontal modes increase with growing bubble size. However, for identical bubble size, the vertical observation gives stronger TS than the horizontal one. Further, TS distribution around mean value is wider with an increase in bubble size, and this distribution is greater in case of the horizontal mode of observation than vertical. It was observed that during bubble rise TS changes for both the vertical and horizontal mode of observation lie within the range of standard deviation of TS measurement; hence, depth is not relevant for TS regression models used in depth up to 6 m.